Indecopi as an autonomous constitutional body: Reasons for the constitutional amendment project - Velásquez, Raffo (2020)
The issue of the independence of competition agencies has been the subject of debate in law in general. Particularly in the different forums organized by the Organization for Economic Cooperation and Development due to the international standard required of such bodies. In this sense, an autonomous constitutional organism is relevant for the proper development of public administration and, consequently, for the fulfillment of the public interest of a State.In this article, the author analyzes whether the Constitution provides reasons to consider Indecopi as a new OCA. To this end, he analyzes how public administrations are organized, why Indecopi would need to be an autonomous agency and if there are constitutional legal reasons that can sustain Indecopi’s interest in having a greater detachment from the government.